Heterogeneous labor earning shock process in finite horizon - Md. Arifur Rahman (Luxembourg Income Study (LIS), 2017)
This paper investigates the importance of heterogeneity in the labor earning shock processes. We analyze the earning shock process for both male and female workers in several countries. We argue that unlike time series analysis, in a life cycle model the forecasting horizon is finite and in finite horizon cross-sectional variance profiles of labor earning shocks display any of five specific shapes. Since our study is based on cross-sectional data, we do not estimate the time series parameters, rather we put emphasis on the shapes of the variance profiles. A linear variance profile implicates highly persistent labor earning shock. Even though the overall variance profile is non-linear, we can show that earning shock is highly persistent and the curvature of variance profile can be explained by the specification of Storesletten, et. al. (2004) and Guiso, et.al. (2002). Moreover, the study of persistence of female labor earning is a novel contribution of this paper. Earlier studies occasionally assume highly persistent female earning, nevertheless, remain silent on providing empirical evidence of female earning shock process.
Keywords: 330; inequality; income distribution; wages; earnings